Cost-benefit analysis of coastal defenses on the Vagueira and Labrego beaches in North West Portugal - Maia, Andreia (2018)
The western Portuguese coast and, in particular, the Aveiro littoral zone has been suffering during the last decades critical morphological alterations, due to the increased rates of coastal erosion. The process is related with the reduced supply of sediments, the rise of the mean sea level, the increasing of storm frequencies and anthropogenic transformations. Aveiro coastal stretch is morphologically characterized by a sandy barrier-lagoon system frequently named as Ria de Aveiro; the barrier has been submitted to a continuous narrowing and topographic reduction that altogether potentiate a significant retreat of the coastline, the erosion of the beaches and over washing. This paper analyses the coastal sector of about 3km length, between Vagueira and Labrego beaches, located at the south of the jetties that protect the access to the Aveiro lagoon. The study includes the behaviour of the erosion in the last 52 years, the projection of the coastline for the year 2020 and an analysis of cost-benefit (ACB) for two scenarios: the present with the existent coastal defenses and another one with the absence of defenses. Were examined aerial photographs taken in different years in order to determine the different shoreline positions, historical trends and mean shoreline retreat. The analysis of the economic viability of the scenarios was carried out based on the calculation of the present value (NPV). The historical (1958- 2010) coastline retreat shows a value of about -3.5m/year; and, if the hydrodynamic conditions remain identical to the present, in 2020 is expected a territory loss of approximately 7ha in semi-natural areas, assuming that the urban areas will continue to be protected. The cost-benefit analysis point out that investment in coastal defense is not economically feasible, in particular with the hard defenses. This situation also occurs if nothing is to be done to preserve the natural and built areas. However, in the latter case the economic losses are smaller. Nonetheless all scenarios and change impacts should be based not only on economic factors but also taking into account the ecological and social importance of the coastal zones. Bearing in mind the present trend and in order to continue to protect the urban front of Vagueira, the existing defenses will have to be maintained and reinforced, which will mean more investment in the near future.